Alkaline modification of the acid residue of incinerated sewage sludge ash after phosphorus recovery for heavy metal removal from aqueous solutions. (15th March 2021) - Wang, Qiming; Li, Jiang-shan; Xue, Qiang; Poon, Chi Sun
Highlights: Recycling method for acid residue after phosphorus recovery of ISSA was proposed. Alkali activation turned the residue into a good adsorbent for heavy metal removal. The synthesized material had a high adsorption capacity of 53.3 mg/g for Pb(II). Abstract: Enriched in phosphorus, sewage sludge ash has been extensively studied and applied as a secondary source for phosphorus recovery. Wet extraction, especially acid washing, is one of the most feasible methods to recover phosphorus from the ash due to its ease of operation, high efficiency and low cost. However, the management of the resultant acid residue was seldom addressed. In this study, special focus was paid to the reuse and recycling of the acid residue by an alkaline activation method. Its adsorption performance towards four different heavy metals in aqueous solutions was evaluated by batch and fixed-bed column adsorption experiments. The obtained material showed a high BET specific area (98.29 m 2 /g) and a total pore volume (0.114 cm 3 /g), and effectively removed Cd(II), Cu(II), Pb(II) and Zn(II) from aqueous solutions with the maximum adsorption capacity of around 26.8, 22.2, 53.3 and 13.5 mg/g respectively. It could be loaded in a fixed-bed column to continuously remove heavy metals especially for Pb(II). The proposed method to recycle the acid residue makes the wet extraction methods designing to recover phosphorus from incinerated sewage sludge complete without the generation of waste, which contributes to circular economy and a sustainable future.